A mechanical and modelling study of magnetron sputtered cerium-titanium oxide film coatings on Si (100) - Patel, S.; Radevski, N.; Mondinos, N.; Zhao, X.; Jack, K.; Veder, Jean-Pierre; Zhou, Z.; Jiang, Z. (Elsevier Science Ltd, 2019)
Ce/Ti mixed metal oxide thin films have well known optoelectrical properties amongst several other physio-chemical properties. Changes in the structural and mechanical properties of magnetron sputtered Ce/Ti oxide thin films on Si (100) wafers with different Ce:Ti ratios are investigated experimentally and by modelling. X-ray Photoemission Spectroscopy (XPS) and X-ray diffraction (XRD) confirm the primary phases as trigonal Ce2O3 and rutile form of TiO2 with SiO2 present in all prepared materials. FESEM imaging delivers information based on the variation of grain size, the mixed Ce/Ti oxides providing much smaller grain sizes in the thin film/substrate composite. Nanoindentation analysis concludes that the pure cerium oxide film has the highest hardness value (20.1 GPa), while the addition of excess titanium oxide decreases the hardness of the film coatings. High temperature in-situ XRD (up to 1000 °C) results indicate high thermal phase stability for all materials studied. The film with Ce:Ti = 68%:32% has a new additional minor oxide phase above 800 °C. Contact angle experiments suggest that the chemical composition of the surface is insignificant affecting the water contact angle. Results show a narrow band of 87.7–95.7° contact angle. The finite element modelling (FEM) modelling of Ce/Ti thin film coatings based on Si(100); Si(110); silica and steel substrates shows a variation in stress concentration.